Influence of Thickness on Optical Properties of (PVA- CoCl2) films - خلفشوقي (University of Thi-Qar Journal of Science, 2019)
(PVA- CoCl2) films with different thicknesses were prepared by casting method. The thickness of the prepared films were 15, 25, 35 and 45 μm .The optical transmission (T %) in the wavelength range 190-900 nm of films deposited was measured. The results show that The absorption coefficient α ‹104 (cm-1) .These films show indirect allowed transitions , the optical energy gap about (4.31 eV) for (15 μm),(4.51 eV) for (25 μm) ,(4.68 eV) for (35μm) and (4.72 eV) for (45 μm). The real and imaginary part of dielectric constant calculated and correlated with thicknesses